A Zn(II)-based pillar-layered metal–organic framework: Synthesis, structure, and CO2 selective adsorption. (15th January 2019) - Zhang, Ya-Huan; Bai, Jinquan; Chen, Ya; Kong, Xiang-Jing; He, Tao; Xie, Lin-Hua; Li, Jian-Rong
Graphical abstract: A new Zn(II)-based pillar-layered MOF has been synthesized and structurally characterized, which shows structural transformation based on the guest removal. The de-guest phase of this MOF also represents selective CO2 adsorption over N2 or CH4 . Abstract: A Zn(II)-based metal–organic framework [Zn3 (TCA)2 (DPE)]·DMF·6H2 O (referred to as BUT-161) has been solvothermally synthesized by the reaction of a tritopic carboxylic acid 4, 4′, 4″-nitrilotribenzoic acid (H3 TCA), an ancillary ditopic pyridine ligand 1, 2-di(4-pyridyl)ethylene (DPE) and Zn(NO3 )2 ·6H2 O. The framework of BUT-161 shows a pillar-layered structure, where two-dimensional (2D) layers constructed from trimeric Zn3 (–CO2 )6 clusters and TCA 3− ligands are topologically (3, 6)-connected net, and the layers are further pillared by the DPE linkers. The resulting 3D framework contains 1D channels along the b axis. Powder X-ray diffraction (PXRD) patterns and gas adsorption studies reveal that the activated phase of BUT-161, as BUT-161a has permanent porosity with a Brunauer-Emmett-Teller (BET) specific surface area of 308 m 2 g −1, although the framework structure shrinks (structure transformation) after guest removal. In addition, it has been found that BUT-161a can selectively adsorb CO2 over N2 or CH4 .